Model Pembelajaran Bahasa Indonesia di Program Studi Bahasa Asing di UIN Syarif Hidayatullah Jakarta - Ahmad Bahtiar; Syihaabul Hudaa; Didah Nurhamidah (Balai Bahasa Sulawesi Selatan, 2026)
This research aims to develop an Indonesian language learning model that is in accordance with the needs of students in the foreign language study program of UIN Syarif Hidayatullah Jakarta. This study explores teaching strategies, teaching materials, and approaches that can accommodate the academic needs of students without neglecting the role of Indonesian as the official language of instruction in higher education. This research uses the Research and Development method with a 4D model (Four-D Model), which includes the Define, Design, Develop, and Disseminate stages. Data was collected through the study of learning documents, observations, lecturer questionnaires, study program head questionnaires, student questionnaires, expert validation, and limited trials. Data analysis techniques are carried out descriptively, qualitatively, and quantitatively through data reduction, data presentation, drawing conclusions, and calculating average scores and eligibility categories. The results of the study show that learning Indonesian language in foreign language study programs requires a more contextual, bilingual text-based, and academic literacy oriented model. This research produced the ABAH Model, namely Authentic, Meaningful, Analytical, and Holistic. The results of expert validation show that this model is in the feasible category with a total average of 4.31. Limited trials showed that the ABAH Model was able to improve student activity, discussion quality, bilingual text analysis skills, and scientific writing skills. Thus, the ABAH Model can be used as an alternative to the relevant Indonesian language learning model for foreign language study programs in universities. AbstrakPenelitian ini bertujuan untuk mengembangkan model pembelajaran Bahasa Indonesia yang sesuai dengan kebutuhan mahasiswa di program studi bahasa asing UIN Syarif Hidayatullah Jakarta. Kajian ini mengeksplorasi strategi pengajaran, bahan ajar, serta pendekatan yang dapat mengakomodasi kebutuhan akademik mahasiswa tanpa mengabaikan peran bahasa Indonesia sebagai bahasa pengantar resmi dalam pendidikan tinggi. Penelitian ini menggunakan metode Research and Development dengan model 4D (Four-D Model), yang meliputi tahap Define, Design, Develop, dan Disseminate. Data dikumpulkan melalui telaah dokumen pembelajaran, observasi, angket dosen, angket kaprodi, angket mahasiswa, validasi ahli, dan uji coba terbatas. Teknik analisis data dilakukan secara deskriptif kualitatif dan kuantitatif melalui reduksi data, penyajian data, penarikan simpulan, serta penghitungan skor rata-rata dan kategori kelayakan. Hasil penelitian menunjukkan bahwa pembelajaran Bahasa Indonesia di program studi bahasa asing memerlukan model yang lebih kontekstual, berbasis teks bilingual, dan berorientasi pada literasi akademik. Penelitian ini menghasilkan Model ABAH, yaitu Autentik, Bermakna, Analitis, dan Holistik. Hasil validasi ahli menunjukkan bahwa model ini berada pada kategori layak dengan rata-rata total 4,31. Uji coba terbatas menunjukkan bahwa Model ABAH mampu meningkatkan keaktifan mahasiswa, kualitas diskusi, kemampuan analisis teks bilingual, serta keterampilan menulis ilmiah. Dengan demikian, Model ABAH dapat digunakan sebagai alternatif model pembelajaran Bahasa Indonesia yang relevan untuk program studi bahasa asing di perguruan tinggi.